Empowering Youth with Brain, Beauty, and Behavior: A Development Economics Perspective - Suci, Stannia Cahaya; Zahara, Vadilla Mutia (MOVE: Journal of Community Service and Engagement, 2025)
This community service activity aims to integrate the concept of Brain, Beauty, and Behavior (3B) into the character development of university students as a foundation for shaping a high-quality generation, particularly through an educational approach within the field of Development Economics. The activity was conducted through an interactive seminar targeted at participants of the “Akang-Teteh Ekbang” selection event, namely selected students who serve as departmental ambassadors. The seminar covered the scope of development economics, career prospects, and the importance of strengthening critical thinking (brain), self-confidence and communication skills (beauty), as well as ethics and social responsibility (behavior) as an integrated foundation for forming excellent and adaptive graduate profiles. The methods applied included material presentation and reflective discussion. The results indicated an increase in academic motivation and participants' understanding of the strategic role of the Development Economics major. These findings suggest the need to strengthen similar programs as part of an integrated strategy for student character and academic development.